Obtention parameters of anacahuita seed protein-isolate and evaluation of its antioxidant and antihypertensive properties - Juárez-Goiz, José Mayolo Simitrio; González-Cruz, Leopoldo; Núñez-Camargo, Diego; Teniente-Martínez, Gerardo; R-Medina, Humberto; Bernardino-Nicanor, Aurea (Acta Universitaria, 2022)
Anacahuita is an underutilized species, because its seeds contain high concentration of protein, which during the isolation process may generate some peptides that could provide nutraceutical properties. For this reason, the evaluation of their chemical and nutraceutical characteristics is needed. The goal of this research was to obtain a protein isolate from anacahuita seeds, as well as to characterize it based on its isoelectric point, molecular weight, in vitro digestibility, and antioxidant and hypertensive activities. The results obtained showed a yield and an in vitro digestibility of 83.8% and 87%, respectively; the isoelectric point was reached at pH 4.0, and its antihypertensive activity was 64%; the IC50 for the antioxidant activity was achieved with 79.6 mg of protein isolate; and a denaturalization process in the protein was observed due to effect of isolation. These results suggest that anacahuita seed proteins have potential to be used as nutraceutical compounds, and their modification could increase their nutraceutical capacity.